Biotherapeutic effect of cell-penetrating peptides against microbial agents: a review. Issue 3 (3rd July 2022) - Sadiq, Idris Zubairu; Muhammad, Aliyu; Mada, Sanusi Bello; Ibrahim, Bashiru; Umar, Umar Aliyu
ABSTRACT: Selective permeability of biological membranes represents a significant barrier to the delivery of therapeutic substances into both microorganisms and mammalian cells, restricting the access of drugs into intracellular pathogens. Cell-penetrating peptides usually 5–30 amino acids with the characteristic ability to penetrate biological membranes have emerged as promising antimicrobial agents for treating infections as well as an effective delivery modality for biological conjugates such as nucleic acids, drugs, vaccines, nanoparticles, and therapeutic antibodies. However, several factors such as antimicrobial resistance and poor drug delivery of the existing medications justify the urgent need for developing a new class of antimicrobials. Herein, we review cell-penetrating peptides (CPPs) used to treat microbial infections. Although these peptides are biologically active for infections, effective transduction into membranes and cargo transport, serum stability, and half-life must be improved for optimum functions and development of next-generation antimicrobial agents. Graphical abstract: uf0001